Diagnostic Utility of Bone Marrow Examination in Chronic Liver Disease Patients Referred For Evaluation of Hematological Derangements - Asif, Naghmi; Hassan, Khalid; Anwar, Bushra (International Journal of Pathology, 2018)
Objective: To see the diagnostic utility of bone marrow examination in patients of chronic liver disease referredfor evaluation of hematological derangements.Material and methods: The study was conducted from July 2009 to July 2011 at the Department of Pathology,Pakistan Institute of Medical Sciences (P.I.M.S), Islamabad. A total of 75 diagnosed cases of Hepatitis C inducedchronic liver disease, referred from different departments of PIMS with various indications for bone marrowexamination were included in the study. All these cases were qualitative PCR-positive for HCV-RNA. Patient whohad already received or were on anti -viral therapy were excluded. Routine blood cell counts were done and laterall the patients were subjected to bone marrow examination. Data was entered on SPSS version 16 and statisticallyanalyzed.